Circulating fibronectin isoforms predict the degree of fibrosis in chronic hepatitis C - Hackl, Norman J.; Bersch, Claus; Feick, Peter; Antoni, Christoph Helmer; Franke, Andreas; Singer, Manfred V.; Nakchbandi, Inaam (Scandinavian journal of gastroenterology, 2010)
OBJECTIVE: Hepatic stellate cells only produce fibronectin isoforms in disease states. The isoform-defining domains can be detected in the blood circulation. This study examines whether circulating levels of fibronectin isoforms show a relationship with liver fibrosis on histology in patients with chronic hepatitis C. MATERIAL AND METHODS: In a prospective study, 50 patients with chronic hepatitis C who underwent a liver biopsy were compared to 50 matched controls and 35 patients with other liver conditions. RESULTS: Circulating levels of the fibronectin isoforms were significantly higher in patients with chronic hepatitis C compared to healthy controls [oncofetal fibronectin (oFN) 2.45 +/- 0.17 versus 1.76 +/- 0.16 mg/l, P < 0.005; extra domain-A (EDA) 1.05 +/- 0.06 versus 0.86 +/- 0.06 mg/l, P < 0.05; and extra domain-B (EDB) 14.55 +/- 0.74 versus 9.31 +/- 0.58 mg/l, P < 0.001], even though total fibronectin was lower (198.9 +/- 3.5 versus 343.6 +/- 14.5 mg/l, P < 0.001). A correlation with the fibrosis score was found for both oFN (r = 0.46, P < 0.005) and EDA (r = 0.51, P < 0.001). The combination of an elevation in both markers (oFN and EDA) in the upper quartile was associated with a specificity of > 99% for predicting significant fibrosis (stages 2-4) and 95% for predicting advanced fibrosis (stages 3-4). A combination of decreased values in the lowest tertile for both markers had a specificity of 94% for excluding significant fibrosis. Based on these findings, 30% of the patients scheduled for a liver biopsy could be correctly classified as having or not having significant fibrosis. The remainder would have to proceed with a biopsy. CONCLUSION: Circulating fibronectin isoforms produced by activated stellate cells represent a viable marker for the presence of significant fibrosis or a lack thereof.